ANNIE DE LEEUW’S STRUGGLE FOR FREEDOM IN JOHANNA REISS’ THE UPSTAIRS ROOM - Titin Kristiyaningsih; Ambar Andayani (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. This study is about Annie de Leeuw’s struggle for freedom in Johanna Reiss’ The Upstairs Room. Annie de Leeuw and her sister, Sini find themselves separated from their Jewish family during the Second World War. The Germans always look for them because they are Jews. Annie struggles to gain her free living like others by hiding in a Gentile family’s small room in upstairs for almost three years. Through the characterization of the main character, this study is analyzed intrinsicly. Apart from intrinsic approach, this study also applies extrinsic approach to strengthen the analysis. The extrinsic approach is needed since it also discussesthe concept of freedom.Annie de Leeuw gains her freedom when they are finally liberated by Canadian troops. Surviving in hiding for a very long time, Annie has almost lost the ability to walk. She gets her freedom in the end after facingmanyhard obstacles in her struggle. It is concluded that freedom is an essential need of human being that has to be struggled. Keywords: struggle for freedom, freedom, character